Trastorno de ansiedad y su afectación en las relaciones interpersonales en una persona de 22 años del cantón Montalvo - Escobar Vargas, Valeria Nathaly (2022)
Human beings are sociable by nature, but the various symptoms displayed by patients with generalized anxiety disorder (GAD) at a cognitive, physical, emotional, affective, and behavioral level tend to affect relationships. For this reason, this study focuses on elucidating the issue of generalized anxiety disorder and its incidence in the interpersonal relationships of a 22-year-old adult. The objective of the research is focused on determining the effect of the disorder on interpersonal relationships. To obtain information, a bibliographical research and a practical approach with the patient were used in different sessions, where the discourse is contemplated. The clinical method, case study and psychometric method were also implemented, for which the following techniques were used: Beck's anxiety inventory and Hamilton's anxiety scale. Likewise, techniques such as clinical interview, direct observation and clinical history were applied. Ultimately, the proposal of a therapeutic scheme to work this type of cases is made, said psychological intervention is based on Aaron Beck's cognitive behavioral therapy, based on the results obtained from the patient from the triggering event that occurred in his childhood, resulting in a presumptive diagnosis of GAD that affected interpersonal relationships.